Interface fracture toughness assessment of solder joints using double cantilever beam test - Loo, Shane Zhi Yuan (2012)
In the current work, a test scheme to evaluate solder joint interface fracture toughness using double cantilever beam (DCB) test has been successfully demonstrated. The obtained results, in terms of critical energy release rate, predict the joint failure based on the principle of fracture mechanics. The results can be used as a materials property in the reliability design of various types of solder-ball joined packages. DCB specimens made of 99.9 wt% copper were selected in the current work. Eutectic Sn-37Pb and lead-free Sn-3.5Ag-0.5Cu solders were used to join two pieces of the copper beams with controlled solder thickness. The test record showed steady propagation of the crack along the solder / copper interface, which verifies the viability of such a testing scheme. Interface fracture toughness for as-joined, extensively-reflowed and thermally aged samples has been measured. Both the reflow treatment and the thermal aging lead to degradation of the solder joint fracture resistance. Reflow treatment was more damaging as it induces much faster interface reaction. Fractographic analysis established that the fracture has a mixed micromechanism of dimple and cleavage. The dimples are formed as a result of the separation between the hard intermetallic compound (IMC) particles and the soft solder material, while the cleavage is formed by the brittle split of the IMCs. When the IMC thickness is increased due to extended interface reaction, the proportion of IMC cleavage failure increases, and this was reflected in the decrease of the critical energy release rate.